Comparison of bluetongue virus detection and quantitation methods in south India - Subhra Subhadra; Subrat Kumar; Veluvarthy VS Suryanarayana; Daggupati Sreenivasulu (Journal of Infection in Developing Countries)
Introduction: Bluetongue (BT), a vector-borne viral disease, primarily affects sheep. Of the 26 serotypes of BTV identified so far, 22 are reported to be circulating in India. Due to an increase in vector population and delays in disease diagnosis, the BT control program heavily relies on rapid and confirmatory diagnosis. Polymerase chain reaction (PCR)-based real-time detection assays may be an ideal method to detect the BTV genome in animal blood at an early stage of infection. Methodology: In this study, a SYBR green-based real-time RT-PCR assay was evaluated, validated, and compared with conventional RT-PCR. The specificity and sensitivity of an assay using BTV-2 RNA extracted from tenfold serially diluted (starting from 1.0 TCID50/mL) cell culture virus was also evaluated. Results: While conventional RT-PCR could detect 3.16×102 TCID50 of virus/mL, the real-time PCR test had a detection limit of 3.16×10-4 TCID50/mL. Melting curve analysis indicated the absence of non-specific amplification (R2 = 0.987). Out of the 32 infected blood samples examined, 24 tested positive for BTV RNA. Seven that were found negative through conventional PCR tested positive through real-time PCR. Conclusions: These results showed that the SYBR green-based real-time PCR assay is rapid, sensitive, and equally specific in the diagnosis of BT in BTV-affected animals.